Дисконтування заборгованості: нюанси обліку та аудиту - Брік, Світлана Володимирівна; Мардус, Наталія Юріївна (My University, 2021)
Дебіторська та кредиторська заборгованості є одними з основних статей балансу підприємства. Інформація про їх розмір, стан та строки погашення є важливою у прийнятті управлінських рішень, адже ефективне управління ними здатне підвищити рівень рентабельності та прибутковість підприємства. Правильність відображення операцій із заборгованістю в обліку набуває особливої актуальності після запровадження механізму визначення об'єкта оподаткування з податку на прибуток на основі даних бухгалтерського обліку. Неправильне відображення операцій у бухгалтерському обліку автоматично призводить до появи податкових ризиків. Норми стандартів бухгалтерського обліку вимагають дисконтувати абсолютно всі довгострокові заборгованості. На дату балансу будь-які довгострокові заборгованості потрібно оцінювати за теперішньою (дисконтованою) вартістю. При цьому питання, як обліковувати різницю між фактичною собівартістю за первісного визнання та теперішньою вартістю на дату складання балансу, залишається відкритим, тому дисконтування заборгованості є темою цієї статті.

Modern market relations require a revision of the accounting system, one of the central elements of which is the accounting of mutual settlements of economic entities. Accounts receivable and accounts payable are one of the main items of the balance sheet of the enterprise, information about their size, status and maturity is important in making management decisions. After all, effective management can increase the level of profitability and profitability of the enterprise. The correctness of the reflection of debt transactions in the accounting becomes especially important after the introduction of the mechanism for determining the object of taxation from income tax on the basis of accounting data. Incorrect reflection of transactions in accounting automatically leads to tax risks. Accounting standards require discounting of absolutely all long-term debts. At the balance sheet date, any long-term debt should be measured at current (discounted) value. In accordance with the provisions (standard) of accounting, the need for discounting on initial recognition of financial assets or liabilities is indirectly regulated by several standards, including provisions (standard) of accounting 10, 11. During the official acquaintance with the provisions (standard) of accounting in the previous version, it could be concluded that discounting is subject only to debt on which interest is accrued. In addition, the provisions on discounts were quite clear only for long-term financial liabilities. However, the question of how to account for the difference between the actual cost at initial recognition and the present value at the balance sheet date remains open. Insufficient attention is paid to the issue of discounting financial assets. It is necessary to answer the following questions: what debts are subject to discounting in accordance with regulations; in which cases the debt is not discounted; how exactly to discount the debt and how to reflect it in the account; what issues arise before the audit in connection with the discounting of debts. Therefore, debt discounting is the subject of this article.
Debt discount: nuances of accounting and auditing
Keywords: дебіторська заборгованість; бухгалтерський облік; фінансова звітність; кредиторська заборгованість; управлінські рішення; операційні цикли; теперішня вартість; discounting; receivables; accounts payable; long-term debt; overdue debt; present value; operating cycle